Effect of Organizational Trust and Job Satisfaction on Employee Engagement and Their Impact on Job Performance - Maslikha, Isna (Dinasti Publisher, 2022)
This pre-research was conducted with the aim of building a research hypothesis using a descriptive method. To find out the variables that affect Employee Engagement and Job Performance, a review of previous research was conducted. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results: 1) Organizational Trust has an effect on Employee Engagement; 2) Organizational Trust has an effect on Job Performance; 3) Job Satisfaction has an effect on Employee Engagement; 4) Job Satisfaction has an effect on Job Performance; 5) Employee Engagement has an effect on Job Performance.